The impact of food labeling on purchasing behavior among Non-Muslim consumers in Klang Valley - Abd Latif, Ismail; Mohamed, Zainal Abidin; Rezai, Golnaz; Kamarulzaman, Nitty Hirawaty (American-Eurasian Network for Scientific Information, 2013)
The purpose of this study is to validate the impact of food labels among non Muslim Malaysian consumer using an extended theory of planned behavior model (TPB). In so doing, the study assessed the direct and indirect effect of food labeling on consumer intention to purchase or otherwise the food products of interest. A stratified random sampling technique was adopted in selecting 795 non Muslim consumers in Klang Valley Malaysia. The results of structural equation modeling supported the adequacy of the proposed model. This study contributes to and extends the understanding of the food labeling and purchasing behavior, identifying the rationales for purchasing of food products with labels that contains information such as Halal logo, ingredients and nutritive value.